Collaborative Religious Mentoring and Counseling in Addressing Adolescent Dating Behavior at MAN 1 Kendari - Fitri, Andi Ulfah Auliaul; Raehang, Raehang; Amalia, Hilda Ayu Melvi; Al-Aqsha, Andi Qadri (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
This study investigates students’ perspectives on dating behavior and examines the collaborative practices between Majelis Ta’lim mentors and guidance and counseling teachers in addressing maladaptive dating behavior at MAN 1 Kendari. Employing a qualitative case study design, data were collected through participatory observation, semi-structured interviews, and document analysis involving mentors, counseling teachers, and female students with prior dating experiences. The findings reveal that most students perceive dating as predominantly negative, citing emotional instability, diminished academic focus, and incongruence with the moral identity of an Islamic school. The study further demonstrates that effective collaboration is realized through an integrated framework of preventive, repressive, and curative interventions that align religious guidance with professional counseling practices. These results highlight the significance of value-based collaboration in fostering emotional regulation, academic engagement, and character development among adolescents in faith-based educational settings. However, the single-site focus and emphasis on female students limit the generalizability of the findings. Future research is recommended to adopt comparative or mixed-methods designs across diverse educational contexts to further assess the sustainability and transferability of collaborative intervention models.